The biomedical student and learning in the age of on-line digital - Cain, Amanda; Shephard, Elizabeth (Henry Stewart Talks, 2019)
Techniques & tools for successful study, 2 main themes for biomedical studies, Similarities between different study situations, Maximising learning before, during & after lectures, Examples for study strategies & tools provided by students, Balancing studying with other endeavours